2009
DOI: 10.1016/j.ejogrb.2009.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Serum relaxin levels are reduced in pregnant women with a history of recurrent miscarriage, and correlate with maternal uterine artery Doppler indices in first trimester

Abstract: CondensationSerum relaxin levels are reduced in pregnant women with a history of recurrent miscarriage, and correlate with maternal uterine artery Doppler indices in first trimester. 3 ABSTRACTObjectives: Defective implantation is a mechanism for recurrent pregnancy loss (RPL). We sought to determine whether the serum expression of human relaxin 2 (RLX) is impaired in women with a history of RPL.Study Design: Employing a prospective case-controlled design we studied 20 pregnant women with a history of RPL and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 25 publications
4
25
0
Order By: Relevance
“…Interestingly, plasma concentrations of relaxin-2 have been shown to be very high during normal human pregnancy (ranging between 500 and 1,500 pg/mL), with peak values in the first trimester that decline in the second and third trimesters. 16 This observation is consistent with the markedly increased production of relaxin from gestational tissue. Outside of pregnancy, as demonstrated in the present study, plasma relaxin concentrations decline sharply and are primarily derived from non-gestational tissue, such as the myocardium.…”
Section: Study Limitationssupporting
confidence: 77%
“…Interestingly, plasma concentrations of relaxin-2 have been shown to be very high during normal human pregnancy (ranging between 500 and 1,500 pg/mL), with peak values in the first trimester that decline in the second and third trimesters. 16 This observation is consistent with the markedly increased production of relaxin from gestational tissue. Outside of pregnancy, as demonstrated in the present study, plasma relaxin concentrations decline sharply and are primarily derived from non-gestational tissue, such as the myocardium.…”
Section: Study Limitationssupporting
confidence: 77%
“…Serum samples had been obtained and aliquoted at 6-8, 10-12, 20, and 34 weeks gestation during a previous study [9]. We excluded women who smoked cigarettes from the study.…”
Section: Methodsmentioning
confidence: 99%
“…We excluded women who smoked cigarettes from the study. Sample sizes were determined as previously described [9]. We estimated that the 20 subjects in each study arm would detect a 10% difference in MMP and TIMP levels between groups with 80% power at the 95% confidence level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies using monkeys have shown that supplementary relaxin in vivo is able to specifically induce a thickening of the endometrium, improved vascularization, and reduced pregnancy loss (Goldsmith et al, 2004;Hayes et al, 2004;Einspanier et al, 2009), consistent with a very positive impact on implantation and placentation. Also in women, it has been shown that there is a good association between mid-pregnancy levels of circulating relaxin, reduced spontaneous abortion, and increased blood flow (Jauniaux et al, 1994;Anumba et al, 2009).…”
Section: Relaxin and The Endometrium In Early Pregnancymentioning
confidence: 99%